Rasio Keuangan Sebagai Alat Ukur terhadap Pertumbuhan Perusahaan - Lucky Hendrata (IPM2KPE, 2022)
This study aims to test and measure whether the ratio of liquidity, activity, and profitability affect the measurement of company growth. The research method used is quantitative research. The research population used is all wholesale trading sub-sector companies that are members of the Indonesian Stock Exchange from 2016-2020. The total population in this study was 34 companies. The technique used in sampling using purposive sampling method with a sample of 11 companies. The results showed, a) the liquidity variable obtained a sig value of 0.994. The sig value is greater than 0.05. The calculated T value of the liquidity variable is -0.008 while the T table value is 2.00; b) the activity variable obtained a sig value of 0.575. The sig value is greater than 0.05. The calculated T value of the activity value variable is -0.564 while the T table value is 2.00; c) the profitability variable obtained a sig value of 0.430. The sig value is greater than 0.05. The calculated T value of the profitability variable is 0.796 while the T table value is 2.00. Simply put, a) liquidity or current ratio has no significance and has a negative relationship with company growth; b) activity or total asset turnover has no significant effect on the company's growth; c) profitability or asset ratios do not have a significant effect and have a negative relationship to the company's growth. Keywords: Analysis, Company Growth, Ratio